A remote sensing assessment of pest infestation on sorghum - Singh D.; Sao R.; Singh K.P. (My University, 2025)
The damage caused by the pest to crop is well known. The major aspects of remote sensing are timely estimates of agriculture crop yield, prediction of pest. Therefore, in this paper, an attempt has been made to investigate the utility and potential application of microwave remote sensing for detection of pest infestation within sorghum field. The studies were made on crop sorghum (Meethi Sudan) that is a forage variety and the pest observed was a species of grasshopper. The beds of crop sorghum were specially prepared for pests as well as microwave scattering measurements. In first phase of study, dependence of occurrence of pests on sorghum plant parameters (i.e., crop covered moist soil (SM), plant height (PH), leaf area index (LAI), percentage biomass (BIO), total chlorophyll (TC)) have been observed and analyzed and it was noticed that pests were more dependent on sorghum chlorophyll than other plant parameters, while climatic conditions were taken as constant. An empirical relationship has been developed between occurrence of pests and TC with quite significant values of coefficient of determination (r 2 = 0.82). These crop parameters are easily assessable through microwave remote sensing and therefore they can form the basis for prediction of pest remotely. In the second phase of this study, several observations were carried out for various growth stages of sorghum using scatterometer for both like polarizations (i.e., HH- and VV-) and different incidence angles at X-band (9.5 GHz). Linear regression analysis was carried out to obtain the best suitable incidence angle and polarization to assess the sorghum TC. VV-pol gives better results than HH-pol and incidence angle should be more than 40° for both like polarizations for assessing the sorghum TC at X-band. A negative correlation has been obtained between TC and scattering coefficient with the r 2 values (0.69 and 0.75 for HH- and VV-pol, respectively). The TC assessed by the microwave measurements was helpful to estimate the occurrence of pests on sorghum. Based on both phase of study an algorithm is proposed to estimate the number of pest on sorghum by remote sensing method. There is a quite good agreement between observed occurrence of pest and assessed occurrence of pest. © 2007.